Oral galvanism related to dental implants - Soung Min Kim (SpringerOpen, 2023)
Abstract Background A range of different chemical interactions can generate an unexpected electronic current in a process called galvanism. Oral galvanism (OG) can also be generated by different chemical actions from diverse intraoral rehabilitated metals, including gold, copper, mercury, titanium, and titanium alloy. The main aim of this manuscript is to review OG, particularly focusing on titanium implants and related metallic materials. We searched the MEDLINE (PubMed), Embase, Scopus, and Google Scholar databases for relevant literature published through December 2019. The keywords included "galvanic current", "galvanism", "galvanic corrosion", "oral galvanism", combined with "oral", "oral cavity", "implant", and "saliva." Results Out of 343 articles, 126 articles that met the inclusion criteria were reviewed. We examined and summarized research on OG through a division into four categories: definition and symptoms, diagnosis with testing methods, galvanic corrosion, and oral precancerous lesions with OG. Conclusions Patients with OG have high oral energy and current, and although this phenomenon may be due to the patient's mental illness, OG due to amalgam or mercury occurs. It is evident that the difference in electron potential caused by different elemental components such as titanium alloy and pure titanium, which are essential for manufacturing the implant fixture and the abutment, and chrome and nickel, which are essential for manufacturing the upper crown, causes OG. Since the oral cavity is equipped with an environment in which electric current can be transmitted easily due to saliva, it is imperative that clinicians review the systemic and local effects of salivation.